Perinatal Subplate Neuron Injury: Implications for Cortical Development and Plasticity - McQuillen, P. S. (Brain Pathol, 2006)
Perinatal brain injury may result in widespread deficits in visual, motor and cognitive systems suggesting disrupted brain development. Neurosensory and cognitive impairment are observed at increasing frequency with decreasing gestational ages, suggesting a unique vulnerability of the developing brain. The peak of human subplate neuron development coincides with the gestational ages of highest vulnerability to perinatal brain injury in the premature infant. At the same time, human thalamocortical connections are forming and being refined by activity‐dependent mechanisms during critical periods. Subplate neurons are the first cortical neurons to mature and are selectively vulnerable to early hypoxic‐ischemic brain injury in animal models. Timing of subplate neuron death determines the resulting defect in thalamocortical development: very early excitotoxic subplate neuron death results in failure of thalamocortical innervation, while later subplate neuron death interferes with the refinement of thalamocortical connections into mature circuits. We suggest that subplate neuron injury may be a central component of perinatal brain injury resulting in specific neurodevelopmental consequences.